Drug transporters : molecular characterization and role in drug disposition - You, Guofeng; Morris, Marilyn Emily (John Wiley & Sons, Inc., 2022)
"Unique in the field of pharmaceutical science, this revised 3rd edition takes into account that knowledge in transporters as drug targets for diseases has expanded. Since publication of the second edition, there have been significant advances in the field: in-depth understanding of membrane transporters in pediatric pharmacotherapy, new insights into the impact of these transporters on drug efficacy and safety, and more sophisticated model systems and sensitive assay methods that have been developed. This edition considers the current advances in the field and includes new chapters on in vitro-in vivo scale-up of drug transport activities, the ontogeny of drug transporters, and the transporters as therapeutic targets for diseases. With newly emerging discoveries in transporter science, this book offers both fundamental and updated knowledge of drug transporters. As a result, this new edition reflects where the field is today and also gives a perspective on the directions for the foreseeable future"-- Provided by publisher.
Keywords: Carrier proteins.; Drug carriers (Pharmacy); Pharmacokinetics.; elektronické knihy; electronic books